On properties of Jacobsthal representation numbers - Amacio, Leonor T. (Animo Repository, 2003)
This thesis is an exposition of the paper Jacobsthal Representation Numbers by A. F. Horadam [7] which appeared in the Fibonacci Quarterly Volume 34, 1996, pages 40-54.